Functional organization of the genome may shape the species boundary in the house mouse - Janoušek, Václav; Munclinger, Pavel; Wang, Liuyang; Teeter, Katherine C; Tucker, Priscilla K (Molecular biology and evolution, 2015)
Genomic features such as rate of recombination and differentiation have been suggested to play a role in species divergence. However, the relationship of these phenomena to functional organization of the genome in the context of reproductive isolation remains unexplored. Here, we examine genomic characteristics of the species boundaries between two house mouse subspecies (Mus musculus musculus/M. m. domesticus). These taxa form a narrow semipermeable zone of secondary contact across Central Europe. Due to the incomplete nature of reproductive isolation, gene flow in the zone varies across the genome. We present an analysis of genomic differentiation, rate of recombination, and functional composition of genes relative to varying amounts of introgression. We assessed introgression using 1,316 autosomal single nucleotide polymorphism markers, previously genotyped in hybrid populations from three transects. We found a significant relationship between amounts of introgression and both genomic differentiation and rate of recombination with genomic regions of reduced introgression associated with higher genomic differentiation and lower rates of recombination, and the opposite for genomic regions of extensive introgression. We also found a striking functional polarization of genes based on where they are expressed in the cell. Regions of elevated introgression exhibit a disproportionate number of genes involved in signal transduction functioning at the cell periphery, among which olfactory receptor genes were found to be the most prominent group. Conversely, genes expressed intracellularly and involved in DNA binding were the most prevalent in regions of reduced introgression. We hypothesize that functional organization of the genome is an important driver of species divergence.
Keywords: Animals; Genetic Speciation; jednonukleotidový polymorfismus; druhová specificita; selekce (genetika); Mice; Polymorphism, Single Nucleotide; Species Specificity; genom; Genome; myši; Selection, Genetic; mouse genome; Reproductive Isolation; speciation; vznik druhů (genetika); zvířata; hybrid zone; reprodukční izolace